Discourses of beauty: An ideological apparatus of women marginalization in Pakistani literature - Ghulam Ali; Uzma Asmat; Muhammad Issa; Ansar Ali (Yayasan Mitra Persada Nusantara, 2026)
The present research aims at deconstructing the ideals of beauty in English literature produced by Pakistani women. It also focuses on demystifying the discursive structures which define a set of normative standards of beauty in a patriarchal society like Pakistan. The study is based on a corpus of twenty novels authored by women. The metaphor of beauty has been demystified by employing FCDA. This research attempts to understand the ways women view the image of female beauty as compared to the perspective of men on female beauty. The research found Adjective-phrase as one of the most constitutive parts of Discourse of beauty. It found that the adjectives like gorgeous, pretty, delicate, elegant, attractive were most frequently associated with the image of woman to constitute her as beauty being. Several discursive strategies in this regard have been employed by both counterparts to maintain the Status quo of societal power in Pakistani patriarchal society. This conceptualization of beauty is so pervasively disseminated in the minds of women that they feel proud of being admired and appreciated by their counterpart. The study also highlights that women are taken as beauty being, a thing, a toy or an instrument to be enjoyed. No doubt, women’s beauty in men’s discourses equates to their physical appearance and sexual object. The same tendency has been highlighted in women discourses which as well reflect that the women are aware of male gaze regarding feminine beauty. The concept of beauty is strictly associated only with women and considered as an inherent trait of an acceptable woman in the society. The phenomenon reiterates the historical and traditional concept of beauty attached only to women. This concept of passivation contributes to women's continued marginalization as inactive beings of society.